Small-molecule agents for cancer immunotherapy - Fang Wang; Kai Fu; Yujue Wang; Can Pan; Xueping Wang; Zeyu Liu; Chuan Yang; Ying Zheng; Xiaopeng Li; Yu Lu; Kenneth Kin Wah To; Chenglai Xia; et al. (Elsevier, 2024)
Cancer immunotherapy, exemplified by the remarkable clinical benefits of the immune checkpoint blockade and chimeric antigen receptor T-cell therapy, is revolutionizing cancer therapy. They induce long-term tumor regression and overall survival benefit in many types of cancer. With the advances in our knowledge about the tumor immune microenvironment, remarkable progress has been made in the development of small-molecule drugs for immunotherapy. Small molecules targeting PRR-associated pathways, immune checkpoints, oncogenic signaling, metabolic pathways, cytokine/chemokine signaling, and immune-related kinases have been extensively investigated. Monotherapy of small-molecule immunotherapeutic drugs and their combinations with other antitumor modalities are under active clinical investigations to overcome immune tolerance and circumvent immune checkpoint inhibitor resistance. Here, we review the latest development of small-molecule agents for cancer immunotherapy by targeting defined pathways and highlighting their progress in recent clinical investigations.